Comparison of altimetric products of Palsar/Alos and Lidar sensors from the Sinmap model (Research, Society and Development, 2020)
The main objective of the study is to analyze and measure the distribution of the Sliding Stability Indices, applying the SINMAP model, using two altimetry products: One from the PALSAR / ALOS sensor and the other from the LIDAR sensor, in the same study area. We sought to evaluate whether the PALSAR sensor product presents a satisfactory and acceptable response for its application in landslide prediction models, in locations that do not have a database, lacking information. It was found that despite the PALSAR product, it does not present the same precision and detail as the LIDAR results, both have several similarities. However, the evaluation of the homogeneity of the data by applying the Coefficient and Determination (R²) and the Pearson Correlation Coefficient (r), as well as the errors using the Mean Absolute Error (EMA), Relative Mean Error (EMR ) and the mean square error (REQM), showed that both products show strong similarity. However, it was considered that the existing DEM in PALSAR / ALOS presents acceptable and convincing results to be applied in the identification of areas susceptible to landslides, in places that do not have a detailed database.